Distributional effects of payment card pricing and merchant cost pass-through in the United States and Canada - Marie-Hélène Felt; Fumiko Hayashi; Joanna Stavins; Angelika Welte (Federal Reserve Bank of Boston, 2020)
Using data from the United States and Canada, we quantify consumers' net pecuniary cost of using cash, credit cards, and debit cards for purchases across income cohorts. The net cost includes fees paid to financial institutions, rewards received from credit or debit card issuers, and the merchant cost of accepting payments that is passed on to consumers as higher retail prices. Even though credit cards are more expensive for merchants to accept compared with other payment methods, merchants typically do not differentiate prices at checkout, but instead pass through their costs to all consumers. As a result, credit card transactions are crosssubsidized by cheaper debit and cash payments. Card rewards and consumer fees paid to financial institutions are additional sources of cross-subsidies. We find that consumers in the lowest-income cohort pay the highest net pecuniary cost as a percentage of transaction value, while consumers in the highest-income cohort pay the lowest. This result is robust under various scenarios and assumptions, suggesting payment card pricing and merchant cost pass-through have regressive distributional effects in the United States and Canada.
Keywords: D12; D31; G21; L81; 330; Regressive effects; rewards; credit cards; interchange fees; pass-through